2009
DOI: 10.1093/gerona/glp051
|View full text |Cite
|
Sign up to set email alerts
|

Life-Span Extension in Mice by Preweaning Food Restriction and by Methionine Restriction in Middle Age

Abstract: Life span can be extended in rodents by restricting food availability (caloric restriction [CR]) or by providing food low in methionine (Meth-R). Here, we show that a period of food restriction limited to the first 20 days of life, via a 50% enlargement of litter size, shows extended median and maximal life span relative to mice from normal sized litters and that a Meth-R diet initiated at 12 months of age also significantly increases longevity. Furthermore, mice exposed to a CR diet show changes in liver mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
271
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(288 citation statements)
references
References 50 publications
15
271
2
Order By: Relevance
“…In support of this interpretation, longevity was reduced in GHR-KO females in which a reduction of body weight produced by litter crowding persisted until the age of 2 years and not in males in which body weight difference disappeared during the second half of life. Increased late life mortality of GHR-KO females raised in large litters contrasts sharply with the pronounced beneficial effect of litter crowding on longevity of normal mice studied by Sun et al (Sun et al 2009) and also differs from the somewhat less clear benefit seen in normal females in the present study. We have no explanation for the much smaller longevity benefit of litter crowding in normal animals in the present study in comparison to the mice studied by Sun et al (Sun et al 2009).…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…In support of this interpretation, longevity was reduced in GHR-KO females in which a reduction of body weight produced by litter crowding persisted until the age of 2 years and not in males in which body weight difference disappeared during the second half of life. Increased late life mortality of GHR-KO females raised in large litters contrasts sharply with the pronounced beneficial effect of litter crowding on longevity of normal mice studied by Sun et al (Sun et al 2009) and also differs from the somewhat less clear benefit seen in normal females in the present study. We have no explanation for the much smaller longevity benefit of litter crowding in normal animals in the present study in comparison to the mice studied by Sun et al (Sun et al 2009).…”
Section: Discussioncontrasting
confidence: 90%
“…Increased late life mortality of GHR-KO females raised in large litters contrasts sharply with the pronounced beneficial effect of litter crowding on longevity of normal mice studied by Sun et al (Sun et al 2009) and also differs from the somewhat less clear benefit seen in normal females in the present study. We have no explanation for the much smaller longevity benefit of litter crowding in normal animals in the present study in comparison to the mice studied by Sun et al (Sun et al 2009). Differences in the genetic background may have been involved, but recent studies in the Miller laboratory in UM-HET animals (produced by the same crosses as those used by Sun et al) also showed only small and sex-specific extension of longevity in response to litter crowding (data not shown).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Mice derived from cross‐fostered crowded litters (CL), in which 12 pups are present (‘CL’ mice), are longer lived than mice from cross‐fostered litters of 8 pups, showing that reduced nutrient availability in the first 3 weeks of life can itself lead to extended lifespan (Sun et al ., 2009). Crowded litter mice have lower levels of IGF‐1 at weaning than controls (Sun et al ., 2009), consistent with the idea that low levels of GH and/or IGF‐1 early in life may have long‐lasting benefits for health and longevity. These findings indicate that some important mechanisms of aging are programmed by endocrine signaling during the first few weeks of development.…”
mentioning
confidence: 99%